Characterization of chemically prepared magnetite nanoparticles - N. K., Devaraj; B. H., Ong; M., Matsumoto (TAYLOR & FRANCIS INC, 2008)
Magnetite (Fe3O4) nanoparticles are being extensively researched as potential building blocks for nanoscaled structures, devices and systems. They exhibit many unique properties due to their dimension that lies in the mesoscopic scale (in between atomic scale and microscopic scale). In addition, it is possible to fine tune the properties of magnetite particles prepared by wet chemical techniques simply by varying the synthesis parameters. Thus, they are widely considered for various applications in fields such as electronics, optoelectronics, biomedicine and medical diagnostics. However, in order to be widely utilized for biomedical and commercial applications, these particles have to be produced at a large scale with low cost, high yield and high reproducibility. Moreover, the particles have to possess uniform properties and narrow size distribution. In this paper, Fe3O4 nanoparticles are prepared under non-oxidized environment using co-precipitation of Fe2+ and Fe3+ with an alkaline base. The effect of preparation variables, such as the stirring rate, stirring period and reaction temperature, on the properties of the nanoparticles are compared using TEM, VSM and XRD.